2017
DOI: 10.3847/1538-4357/aa6218
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Analytical Model for Rocky Planet Interiors

Abstract: This work aims at exploring the scaling relations among rocky exoplanets. With the assumption of internal gravity increasing linearly in the core, and staying constant in the mantle, and tested against numerical simulations, a simple model is constructed, applicable to rocky exoplanets of core mass fraction (CMF) ∈ 0.1 ∼ 0.4 and mass ∈ 0.1 ∼ 10M ⊕ . Various scaling relations are derived: (1) core radius fraction CRF ≈ √ CMF, (2) Typical interior pressure P typical ∼ g · M p · R 2 p . These scaling relations, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Colors represent the assumed mass of the planet in each run. The empirical scaling relation of CRF ≈ CMF 0.5 proposed inZeng and Jacobsen (2017) is shown as a red dashed line. (b) Comparison of our calculated mass and radius values (symbols as inFigure 3) to the Z16 model for CMF = 0.25 (red dashed line), 0.33 (dashed green line), and 0.45 (dashed black line).…”
mentioning
confidence: 99%
“…Colors represent the assumed mass of the planet in each run. The empirical scaling relation of CRF ≈ CMF 0.5 proposed inZeng and Jacobsen (2017) is shown as a red dashed line. (b) Comparison of our calculated mass and radius values (symbols as inFigure 3) to the Z16 model for CMF = 0.25 (red dashed line), 0.33 (dashed green line), and 0.45 (dashed black line).…”
mentioning
confidence: 99%
“…But for internally differentiated rocky planets, its value is a little lower. In this sense, Zeng & Jacobsen (2017) showed that for both the Earth and Earth-like rocky planets, its value is approximately equal to 1/3. In consequence, we can take ξ 1 = 2/5 and ξ 2 = 1/3.…”
Section: Initial Conditions and Physical Parametersmentioning
confidence: 97%
“…The model then calculates the minimum and maximum core radius fractions for which a marginal CRF can be sampled. The core radius fraction is related (Zeng & Jacobsen 2017) This translates to a CMF of 78% ± 11% using this model. As an alternative method, we characterized the internal structure of HD 137496 b considering a pure-iron core, a silicate mantle, and a pure-water layer using a Bayesian inference analysis.…”
Section: Modeling Of the Internal Structure Of Hd 137496 Bmentioning
confidence: 99%